Implementasi Metode Case Based Reasoning untuk Mendiagnosa Penyakit Lambung - Yayang Eluis Bali Mawartika (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2021)
The more advanced times cause people to be busier and longer pay attention to their eating patterns. Irregular eating patterns and stress due to busyness can cause stomach disease, such as gastritis, gerd, and peptic ulcers. Complaints and symptoms of disease felt by people with gastric disease vary, so it is difficult to know the type of disease in his suffering. Most people only know what that gastric disease is called gastritis, whereas gastric disease is of various kind. Therefore, there needs to be an anlysis that can diagnose gastric disease. This study uses the Case Based Reasoning (CBR) method to diagnose gastric ailments, by looking for closeness or similarity between symptoms in old cases with symptoms in new cases. Criteria or symptoms used for the diagnosis process include pain in the pit of stomach, bloating, nausea, vomiting, lower chest pain, belching, feeling full quickly, and the stomach feels full. While gastric disease variables consist of gastritis, gerd, and peptic ulcers. The results showed that the calculation of the value closeness between new cases and old cases is close or similar, this shows that the Case Based Reasoning method can diagnose gastric disease well.